On the rating system in alpine skiing racing: Criticism and new proposals - Maisano, D.; Botta, A.; Franceschini, F. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
Like most sports, alpine skiing has international regulations - its regulations specifically designed by the FIS, that is, the Fédération Internationale de Ski or International Ski Federation- aimed at coordinating competitions and rating athletes. FIS points, as they are called, represent the core of the rating system, as they facilitate the rating of athletes involved in competitions for each of the five alpine skiing disciplines, that is, slalom, giant slalom, super-G, downhill, and combined. The objective of this article is to analyse the current rating system, giving special attention to the FIS points` construction and updating system and focusing on the potential weaknesses. Two major weaknesses emerge from this analysis: (1) the questionable update process of the FIS points, based on the average of the best two results obtained in a discipline of interest, and (2) the lack of a general rating of athletes based on their eclecticism, that is, the ability to obtain good results in as many different disciplines as possible. The second part of the article presents some proposals for sorting out the above weaknesses. The description therein is supported by several practical examples, based on real and hypothetical data.